Takotsubo cardiomyopathy mimicking acute ST-segment elevation myocardial infarction in a 28-year-old woman - Dubey, Laxman; Sharma, Sanjib Kumar; Gautam, Samir; Dhungel, Sachin; Laudari, Shankar (Journal of Advances in Internal Medicine, 2014)
DOI Takotsubo cardiomyopathy is a rare type of nonischemic cardiomyopathy accompanied by a transient ballooning and akinesis of the apical segment of left ventricle. Here, we report a 28-year-old woman who presented with acute chest pain after an emotional stress. Electrocardiography showed STsegment elevation in leads II, III, aVF, V3-V6. Echocardiography, coronary angiography and left ventriculography showed typical features of Takotsubo cardiomyopathy. DOI: http://dx.doi.org/10.3126/jaim.v3i1.10703 Journal of Advances in Internal Medicine 2014;03(01):38-41